Comparison of mechanical and corrosion properties of 7050 aluminum alloy after different laser shock peening. (July 2022) - Guo, Wei; Wang, Hao; He, Guangzhi; Peng, Peng; He, Dongsheng; Han, Guofeng; Yan, Jianfeng
Highlights: The effects of NLSP and FLSP on mechanical and corrosion properties were examined for 7050 aluminum alloy. The comprehensive properties were induced similarly and essentially near the impacted surface for both NLSP and FLSP. Different microstructures or properties of internal parts were attributed to the attenuation of shock waves. Abstract: Nanosecond laser shock peening (NLSP) with over-layers is attractive because it generates grain refinement and compressive residual stress for 7050 aluminum alloy. Femtosecond laser shock peening (FLSP) without any over-layers is advantageous in terms of selective processing. However, few studies have focused on the feasibility of FLSP under atmospheric conditions for 7050 aluminum alloy, and the comprehensive analysis of properties improvement between NLSP and FLSP remains unexplored. Here, the effects of NLSP on mechanical and corrosion properties were examined with over-layers for 7050 aluminum alloy. Results of FLSP were presented for comparison under atmospheric conditions. Based on detailed observations at the micrometer and nanometer scales, it was found that the surface roughness, hardness, compressive residual stress, and corrosion resistance were induced similarly and essentially near the impacted surface. Internally, the hardness and residual stress decreased slowly after peaking at the impacted surface for NLSP. During FLSP, unchanged microstructures or properties were preserved in the internal parts. These were attributed to the changes in attenuation characteristics of the shock wave during NLSP and FLSP. These findings can be used for property improvement with different focus (surface or/and internal mechanical and corrosion properties) for wide spectrums of metals and alloys.